Effect of ovarectomy of females and oestrogen administration to males during the neonatal critical period on salt intake in adulthood in rats - Krecek, J (Physiologia Bohemoslovaca, 1978)
The effect of interference in the neonatal critical period on water and salt solution (3% NaCl) intake by adult rats given a free choice of these fluids was studied. Consumption was expressed per animal, per 100 g body weight and as the NaCl concentration in the total daily fluid intake volume [NaCl]I. Newborn female rats were ovarectomized or sham-ovarectomized. Ovarectomy markedly reduces consumption and [NaCl]I in adulthood and brought these values close to the values in normal males. Newborn male rats were injected with 1 mg oestradiol propionate dissolved in oil or just with oil. Oestradiol propionate severely inhibited growth, but produced no changes in fluid intake per animal. The [NaCl]I values were likewise unaltered, but owing to the lower body weight comsumption values per 100 g b.w. were higher in rats given oestradiol propionate than in those given oil. The relationship of the given growth changes to the regulation of salt intake and to hypothalamic function and its sexual correlates is discussed.
Keywords: Rats; Animals, Newborn; pití; Drinking; Sodium Chloride; mužské pohlaví; novorozená zvířata; stravovací zvyklosti; krysa rodu Rattus; Saline Solution, Hypertonic; ženské pohlaví; zvířata; Estradiol; ovarium; Ovary; chlorid sodný; hypertonický solný roztok; Feeding Behavior; Female; estradiol; Male; Animals